SYLVAIN HUGEL (2014) Grasshoppers of the Mascarene Islands: new species and new records (Orthoptera, Caelifera). Zootaxa, 3900 (3): 399–414. - Hugel, Sylvain (Zootaxa, 2015)
The date of publication for this paper should be 23 Dec. 2014 instead of 23 Dec. 2015. The year of copyright on the first page and the year in footers and headers on the rest of pages should be 2014 instead of 2015.